JILBAB DALAM JARINGAN BISNIS BIKA AMBON ZULAIKHA DAN BOLU MERANTI DI KOTA MEDAN - ASWAN JAYA (LP2MTBM MAKARIOZ, 2019)
This study aims to answer the questions (1) whether the background of the use of the veil for waiters working in the business of Bika Abon Zulaikha and Bolu Meranti in Medan is an ideological order (Islamic law) or a market strategy. (2) What is the impact of the use of the hijab on consumer interest and buying levels on the culinary products. This research uses qualitative methods with descriptive analytical data. The researcher became the main instrument in this research project. This study will provide an overview of the phenomenon of the hijab in the culinary business in the city of Medan. Female owners and workers at Bika Ambon outlets Zulaikha and Bolu Meranti are the primary sources in collecting data through interview, observation and documentation techniques.The results showed that (1) Headscarf of female workers is a policy imposed by culinary investors for two purposes, first, veiling is the implementation of marketing management management in order to attract the largest Muslim consumers in Medan. Second, veiling to maintain a clean and hygienic environment for all culinary products. Especially at the Bika Ambon Zulaikha outlet, veiling has moved towards ideological awareness (sharia). The veiled awareness of every female worker has 3 (three) levels of awareness and understanding, first, ideological awareness and understanding long before work. Second, find awareness and understanding of the hijab after work. Third, the awareness and understanding of hijab is limited as a head covering to maintain the cleanliness of culinary products. (2) Jilbab also contributes in building the perception of Islamic consumers to shop at culinary outlets. That Islamic consumers have confidence and comfort in hygienic and halal guarantees when shopping for culinary at outlets where workers wear headscarves.